Exploring the role of resources in ethnic minorities' adoption of Information and Communication Technology in preserving their cultural identity in Malaysia - Gill, Sarjit S.; Talib, Ahmad Tarmizi; Choo, Yeong Khong; Kunasekaran, Puvaneswaran (Canadian Center of Science and Education, 2016)
The aim of this article is to investigate the current conditions of the adoption of Information and Communication Technology (ICT) in preserving cultural identity among the ethnic minorities in Peninsular Malaysia. ICT plays a crucial role in the present knowledge-based globalization era and the usage has become a basic necessity for all members of the society in managing their daily lives. It has pervaded every aspect of human life and has significantly changed the manner in which society communicate and interact with one another. This is particularly important as the ethnic minorities in Malaysia inevitably facing the great challenges of losing their cultural identity through the assimilation process into the larger mainstream society. ICT appear as an alternative which help in enhancing the efforts for cultural preservation. The penetration of ICT in ethnic minority everyday life has directly or indirectly provides a platform for them to express and share their ideas, thoughts, perceptions and knowledge about their existing culture. However, are the ethnic minorities have sufficient resources to adopt ICT to preserve their culture is still unexplored. The extent of the ethnic minorities' awareness of the advantages of ICT to preserve their cultural identity is still questionable.